Discovery of a novel species of the genus Perionyx Perrier, 1872 (Clitellata: Megascolecidae) from Manipur, North-Eastern Region, India - Tiwari, Nalini; James, Samuel W.; Gupta, Neelima; Yadav, Shweta (Zootaxa, 2025)
The study introduces a new species, Perionyx browantlerus Tiwari & Yadav sp. nov. identified in the north-eastern region of India, particularly in Manipur State. It possesses two pairs of mid-ventral spermathecal pores located in the intersegmental furrow of segments vii/viii/ix, possessing a vestigial gizzard, exhibiting holandric traits, and lacking pineal setae. Perionyx browantlerus Tiwari & Yadav sp. nov. stands out from other similar species because of its adiverticulate spermathecae. Furthermore, another interesting species Perionyx sp. nov.? 1 was also found, which is characterized by a unique "V"-shaped longitudinal oblong impression situated above the male pore, which extends from each papilla. Unfortunately, the single specimen with malformed segmentation prevents it from being described as a new species.